Group-based body psychotherapy improves appreciation of body awareness in post-treatment cancer patients: A non-randomized clinical trial - Grossert, Astrid; Meffert, Cornelia; Hess, Viviane; Rochlitz, Christoph; Pless, Miklos; Hunziker, Sabina; Wössmer, Brigitta; Geuter, Ulfried; Meinlschmidt, Gunther; Schaefert, Rainer (Frontiers in Psychology, 2023)
Introduction: Cancer-related impairments often co-occur with bodily disturbances. Body psychotherapy (BPT) can improve bodily well-being, yet evidence in cancer survivors is scarce. Hence, we aimed to evaluate whether blended group BPT alleviates bodily disturbances in post-treatment cancer patients. Methods: We conducted a bi-center study (registered in ClinicalTrials.gov, under No. NCT03707548), applying a pre-post convergent parallel design of weekly group BPT interspersed with smartphone-based ambulatory interventions using a waiting-period comparator. We included patients with completed curatively intended treatment for malignant neoplasms, suffering from bodily disturbances. The primary outcome was body image disturbances. Secondary outcomes were experiencing and appreciating body awareness, mental well-being, and health-related quality of life. Results: Forty patients (mean age 51.7 years) attended group BPT. Mixed-effect linear regression models contrasting intervention with the waiting period did not show statistically significant differences regarding the primary outcome (Pre-post difference contrasts: 1.44, 95% confidence interval (CI): -1.51 to 4.93, p=0.339). However, patients showed greater improvements in appreciating body awareness, measured by the ‘Body Mindfulness Questionnaire’ (BMQ), from pre- to post-intervention as compared to the waiting period (pre-post difference contrasts: 7.31 95% CI: 4.15 to 10.47, Bonferroni-Holm corrected q=0.0002). Discussion: We found no evidence that blended group BPT was effective in improving body image disturbances in post-treatment cancer patients, but found indications for an increase in body awareness appreciation.